Community Reading Park (TBM) Sirnarasa Village as a Medium to Increase Community Literacy Interest in Efforts to Empower the People of Sirnarasa Village - Al-Farizi, Farhan Fauzan; Bhudiman, Budy (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
(TBM) Community Reading Park is one of the centers of community learning activities which can be an alternative in facilitating access to reading materials and meeting people's information needs so that people with middle to lower economies located in remote areas whose access is difficult to reach will be easier to obtain the reading materials they need. One of the efforts that can be done in community empowerment is through Community Reading Gardens (TBM). This is supported by a statement conveyed by the Directorate of Community Education that one of the benefits of community reading gardens (TBM) is that they can increase community empowerment in various fields. Community empowerment starts from the concept or word empowerment. Etymologically, empowerment comes from the root word